The Role of Growth Differentiation Factor 15 in Energy Metabolism - Chang, Joon Young; Hong, Hyun Jung; Kang, Seul Gi; Kim, Jung Tae; Zhang, Ben Yuan; Shong, Minho (Diabetes & metabolism journal, 2020)
Growth differentiation factor 15 (GDF15) is receiving great interest beyond its role as an aging and disease-related biomarker. Recent discovery of its receptor, glial cell line-derived neurotrophic factor (GDNF) family receptor α-like (GFRAL), suggests a central role in appetite regulation. However, there is also considerable evidence that GDF15 may have peripheral activity through an as-of-yet undiscovered mode of action. This raises the question as to whether increased GDF15 induction during pathophysiologic conditions also suppresses appetite. The present review will briefly introduce the discovery of GDF15 and describe the different contexts under which GDF15 is induced, focusing on its induction during mitochondrial dysfunction. We will further discuss the metabolic role of GDF15 under various pathophysiological conditions and conclude with possible therapeutic applications.